Inferring species boundaries using acoustic and morphological data in the ground cricket genus Gymnogryllus (Orthoptera: Grylloidea: Gryllinae). Issue 8 (17th November 2018) - Tan, Ming Kai; Yong, Crystal Yun Han; Ingrisch, Sigfrid; Ahmad Sah, Hanyrol H.; bin Haji Abdul Wahab, Rodzay; Johns, Philip Michael
Abstract : An important function of song production by male crickets is to attract conspecific females. These sound signals can be used to infer species boundaries as they can provide indirect evidence for reproductive isolation. However, many studies of orthopteran diversity in South-east Asia are based mainly on morphology and only occasionally acoustics. As such, there is a lack of information on how acoustic data can be congruent with morphological data when used to delineate species. Crickets of the genus Gymnogryllus (Grylloidea, Gryllidae), are such an example. Gymnogryllus are relatively speciose, but their calling songs have not been studied. We collected specimens and calling songs of five Gymnogryllus species from South-east Asia. The acoustic parameters of the calls, along with male tegminal venation and morphology genitalia, were compared. All data types showed congruency in distinguishing G. sylvestris and G. leucostictus from each other and from the other species. Inferring species boundaries for G. angustus, G. malayanus, and G. unexpectus using acoustics and tegminal morphometry proves to be more challenging. While acoustics, tegminal morphometry, and genital morphology are likely to be useful for inferring species of Gymnogryllus from different species groups, greater coverage of taxa is needed to resolve taxonomy of closely related Gymnogryllus.